Multiple-iteration springback compensation of tailor welded blanks during stamping forming process. (15th July 2016) - Wang, H.; Zhou, J.; Zhao, T.S.; Liu, L.Z.; Liang, Q.
Abstract: The forming and springback of tailor welded blanks (TWBs) are more complicated than those of conventional sheet metals because of the influence of weld seam. The current study investigated the microstructure and fracture of TWBs through metallographic microscopy and scanning electron microscopy. Tensile tests show that thin and thick materials possess similar mechanical properties. The maximum elongation and yield strength of the TWBs decrease, whereas the tensile strength of the TWBs is larger than that of the base materials. We proposed the use of multiple-iteration springback compensation to improve the accuracy of springback compensation for the TWBs. The simulation of the entire forming processes, which includes drawing, trimming and piercing, as well as springback analysis, was used to explore the stamping forming of the TWBs by automotive floor reinforcement. Forming parameters were optimised in drawing process. In addition, springback calculation was performed to predict the springback of the formed part. Furthermore, multiple-iteration springback compensation was applied to drawing tools and verified by experiments. The experimental results agree with the simulation results. Graphical abstract: Highlights: Multiple-iteration springback compensation has proven to be effective in compensating springback for tailor welded blanks. The weld seam decreases the maximum elongation and yield strength of tailor welded blanks. The qualified rate of production can reach 75% by using the proposed method at the first time of die tryout. The proposed method can reduce the number of compensation and tryout time.